2017
DOI: 10.1002/alr.22060
|View full text |Cite
|
Sign up to set email alerts
|

The association of air pollutants and allergic and nonallergic rhinitis in chronic rhinosinusitis

Abstract: Our results suggest that small inhalant pollutants may contribute to nonallergic symptomatology in patients with and without nasal polyps. Regardless of allergy status, BC may play a role in CRS symptom severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 36 publications
2
46
0
Order By: Relevance
“…However, as discussed before, no association was found in the study by Annesi-Maesano et al 15 between air pollution levels and score of allergic rhinitis. In the study by Mady et al, 16 a positive correlation was found between exposure to black carbon and some symptoms of rhinitis, regardless of allergic sensitization status, and no results were available for PM 2.5 . Furthermore, this study was based on a small selected sample of patients with disease, without formal statistical analyses.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…However, as discussed before, no association was found in the study by Annesi-Maesano et al 15 between air pollution levels and score of allergic rhinitis. In the study by Mady et al, 16 a positive correlation was found between exposure to black carbon and some symptoms of rhinitis, regardless of allergic sensitization status, and no results were available for PM 2.5 . Furthermore, this study was based on a small selected sample of patients with disease, without formal statistical analyses.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, an American study examined the relationship between PM 2.5 (airborne particulate matter with an aerodynamic diameter of < _2.5 mm) and black carbon and rhinitis in 125 patients with chronic rhinosinusitis with and without polyps. 16 They found significantly higher exposure levels of PM 2.5 and black carbon among participants without allergic sensitization compared with those with allergic sensitization, and also found an association between black carbon and nonallergic symptoms of rhinitis. In a previous study, we found no consistent evidence for an association between long-term exposure to air pollution and incidence of rhinitis, whether allergic or nonallergic.…”
mentioning
confidence: 94%
“…Several studies have been published on the effects of PM on the upper airway; for example, long-and short-term exposure to PM can lead to allergic rhinitis [24,25]. PM has also been shown to cause non-allergic symptoms in rhinosinusitis patients [26]. In cell experiments, PM exposure was observed to interfere with the barrier function of the epithelial layer by disintegrating the tight junctions of nasal epithelial cells [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cross-sectional sampling may obscure whether some of the observed differences in subject clusters represent a temporal continuum of specific endotypes as they develop over time. Given the observed inflammatory complexity, together with other potential sources of influence in determining disease subtypes such as genetic ( 34 ) and life history factors ( 35 , 36 ), many more subjects measured over more variables (or more refined variables) and at multiple time points will be necessary to clearly delineate between true endotypes of CRS and to subsequently draw robust conclusions from comparisons.…”
Section: Discussionmentioning
confidence: 99%